SISTEM PAKAR DIAGNOSA PENYAKIT PADA AYAM DENGAN METODE FORWARD CHAINING - Wahyudi, Jusuf; Utami, Feri Hari (Jurnal Media Infotama, 2011)
is chicken. Chicken had a variety of illnesses. For Some farmers who want to raise chickens especially lay people hit by several problems one of which is a disease. Required to diagnose a disease symptoms appear on the body of the chicken. Necessary seriousness and quick action before it was too late and suffered losses.Therefore, this program is designed to help the farmers in getting some information about chicken diseases. The sooner the disease is known, then the sooner they can prevent it. Identification techniques chosen the chicken disease because the symptoms of common illnesses suffered by chickens are relatively easy to observe and relatievely safe to do by anyone.Applications developed using Visual basic 6.0 and Microsoft Access as the database. Inference method used is a forward chaining, the inference prosess that initiates the search of the premises or in the form of input data lead to the conclusion that the symptoms of the illness conclusions and provide solutions regarding the treatment and prevation advice based on the symptoms observed.